Zoning of the coastal area in Brgy. Baring, Olango Island, Cebu using multiple-criteria suitability analysis - Cerna, Michael Andrew M. (University of the Philippines in the Visayas, 2007)
The Baring CRM marine sanctuary located at Barngay Baring, Olango Island, Cebu was zone based on coral morphology and resource use. Coral morphology was assessed by determining conservation class based on the r-K-s method Coral morphology was assessed using the video transect survey (AIMS 2002). Five 50m transects of 50m inervals were laid parallel to the coastline at 5m depth (shallow transects), and another 5 transects of the same length and interval were laid at 10m depth (deep transects). Results showed that the MPA had a minimal average hard coral cover of 2.1%, and 97.9% of the area was mostly dominated by dead corals, deal coral algae, soft corals, spongers, algae, rubble, sand, silt, rock and others (miscellaneous cover). Based on the r-K-s method, the very poor hard coral cover of 2.1% generally classified the MPA under conservation class 1, which makes it not ideal for conservation. The MPA was also zoned based on the different existing resource uses : gleaning/bathing area, panggal or fish trap area, and hook and line fishing area. Rcommendations include planting coral fragments to help revive coral population in the Area. Strict implementation of the no-take zone rule in order to keep the area undisturbed, giving the MPA a time to 'heal' and recover. A comprehensive MPA management plan should also be formulated as a guide to the efficient and effective management f the Baring CRM marine sanctuary.